2015
DOI: 10.4238/2015.may.18.21
|View full text |Cite
|
Sign up to set email alerts
|

Pre-B-cell colony-enhancing factor is markedly elevated in childhood hemophagocytic lymphohistiocytosis

Abstract: ABSTRACT. Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening syndrome involving a final common pathway of hypercytokinemia, in which tumor necrosis factor (TNF)-a, interferon (IFN)-g, and soluble interleukin 2-receptor-alpha (sIL-2Ra) are the key cytokines. Pre-B-cell colony-enhancing factor (PBEF) is an inflammatory cytokine involved in several inflammatory diseases. However, its role in HLH is unknown. In this study, we examined the role of PBEF in HLH. Plasma was collected from 22 children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Only few studies analyzed NAMPT in the context of inflammatory processes in childhood [17,18]. We had previously shown, that mainly mono- and granulocytes secrete circulating NAMPT and that mildly elevated leucocytes in obesity may contribute to the phenomenon of slightly increased NAMPT levels in low-grade inflammation in obesity [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few studies analyzed NAMPT in the context of inflammatory processes in childhood [17,18]. We had previously shown, that mainly mono- and granulocytes secrete circulating NAMPT and that mildly elevated leucocytes in obesity may contribute to the phenomenon of slightly increased NAMPT levels in low-grade inflammation in obesity [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are only few studies focussing on NAMPT in inflammatory states during childhood [17,18]. We have evidence indicating that NAMPT is elevated in childhood obesity and its corresponding low-grade inflammation [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, Japanese controls had a lower serum sIL2R in children and in adults with ages similar to our series 7 . In China, Gao et al 8 too reported low levels of sIL2R in children aged 2-3 yr. Two reports used the same manufacturer as the present study, Zhao et al 9 described serum sIL2R in Chinese children aged 3-12 yr similar to the present study, while Deveci et al 10 reported considerably lower sIL2R than the present study 9 10 ( Table V ). Thus, both children and adults from India seem to have higher serum sIL2R concentrations than most reports.…”
Section: Discussionmentioning
confidence: 98%
“…This has shown a better specificity because with remission it touches the baseline levels, as compared to IL2 receptor levels which stays mildly elevated for some time. 48 Hybrid immunotherapy is a new treatment modality which is being tried in few centers where steroid, etoposide and ATG are being used. Other regimens with the primary agent being alemtuzumab and tocilizumab (IL-6 receptor inhibitor) are being studied in France and Philadelphia respectively.…”
Section: Hematopoietic Stem Cell Transplant (Hsct)mentioning
confidence: 99%